The Effect of Capital Structure on Company Value: Dividend Mediation on the Kompas 100 Indonesia Index - Ni Luh Wiwin Andayani; I Nyoman Nugraha Ardana Putri; Sunitha Vijayakaumaran (Tinta Emas Institute, 2023)
The establishment of a company certainly has clearly organized and directed goals. The company's first goal is to achieve maximum profits or maximum profits. This research aims to determine the effect of capital structure on company value with dividends as an intervening variable on the Kompas 100 index on the Indonesian stock exchange. The type of research is quantitative research with a causal associative approach. The sample used in this research was 13 companies with 91 observation data. The data collection method used was a survey sample. The data analysis technique uses descriptive statistical analysis, normality test, classic assumption test consisting of path analysis and mediation test (sobel test). The analysis tool in this research uses SPSS (Statistical Package Social Sciences). The results of this research show that capital structure has a positive effect on company value. Dividends have a positive effect on company value, while capital structure does not affect dividends. Capital structure does not affect company value. This is in accordance with the theory of the Modigliani-Miller (MM) Approach to Tax which argues that increasing debt can reduce the tax obtained by the company because paying interest on the company's debt will reduce the amount of the company's taxable income so that it can save on tax costs and will increase the value of the company.